Antifungal Effect of Hydrogen Peroxide on Catalase-Producing Strains of Candida spp. Issue 2 (1995) - Larsen, Bryan; White, Sandra
Abstract : Objective: Clinical isolates of Candida were tested for the presence of catalase and susceptibility to hydrogen peroxide. Methods: MIC was tested by broth dilution technique and catalase was determined by a spectrophotometric procedure. Results: All 38 strains tested were inhibited by hydrogen peroxide in concentrations ranging from 4.4 to 88 mM/l, with non-albicans isolates generally requiring higher concentrations of hydrogen peroxide for inhibition. Growth media consisting of glucose and protein diminished the antifungal effectiveness of hydrogen peroxide, as did the presence of hemoglobin, in incubation mixtures. However, hydrogen peroxide exerted greater inhibition at pH 4 than at pH 7. Although all Candida isolates tested possessed catalase, there was no apparent correlation between the catalase activity of individual isolates and the minimal antifungal concentration of hydrogen peroxide. Conclusions: This study suggested that, despite the production of catalase by vaginal microorganisms, hydrogen peroxide may exert a regulating influence which may be further modified by the proteins found in the vaginal milieu.